Synonimic Words Figured Out Alone (maybe just with a little help of one's friends) - Jelaska, Zrinka (2000)
Learning to distinguish between synonymous words and phrases of his or her mother tongue, a person may be guided by listed key differences, such as the ones found in good dictionaries. But if such a dictionary, as well as time consuming research, is unavailable, there is a lot one can achieve through reflection and/or discussion with a few speakers. Knowing one's mother tongue provides one with necessary data and judgement to choose the most convincing answers. The thing to be learned are methods to sort them out. This paper provides an analysis of solo routes to understanding the key meaning differences between closely related words, including the ones with obvious syntactic consequences. The data will include contrastive examples from Croatian, English and German.
Projekt MZOS
ENG